Co-infection with HIV associated with reduced vulnerability to symptoms of depression during antiviral treatment for hepatitis C. (July 2017) - Fialho, Renata; Pereira, Marco; Harrison, Neil; Rusted, Jennifer; Whale, Richard
Abstract: In this prospective study, we examined new-onset major depressive disorder (MDD) and the differential expression of depressive symptoms in a sample of 132 HCV mono-infected and 40 HIV/HCV co-infected patients initiating pegylated interferon-based treatment, including protease inhibitor therapy. The semi-structured clinical interview (SCID-I) was used to assess MDD. Severity of depressive symptoms was assessed using the Hamilton Depression Rating Scale. Of the total sample, 60 patients (34.9%) developed SCID-I defined MDD during antiviral treatment. The proportion of HCV mono- and HIV/HCV patients developing MDD during treatment was not significantly different (37.9% vs. 25%; p =0.185). In both groups, there was a significant increase in HAMD total score from baseline to week 4, and a significant decrease between week 24 and 6 months post-treatment cessation. The greatest increase was observed in the symptoms of the neurovegetative syndrome. HCV mono-infected patients reported higher scores than co-infected patients, particularly impaired activity and somatic symptoms, but the differences were only significant at week 12. The finding that co-infected patients appear less vulnerable to the development of depressive symptoms during HCV treatment than HCV mono-infected patients warrants further exploration, including a thorough analysis of the biological and psychosocial factors associated with this emergence. Highlights: High prevalence of new-onset depression during antiviral treatment for hepatitis C. Co-infected patients are less vulnerable to the development of depressive symptoms. Depressive symptoms remit after cessation of interferon-α exposure. A comprehensive management of somatic symptoms of depression is needed.